The role of technical and vocational education and training (TVET) in human capital development - 284970 Mohamad Zhurad Haron; Muhammad Rashid Rajuddin; Fakulti Pendidikan (2008)
Thesis (Sarjana Pendidikan (Teknik dan Vokasional)) - Universiti Teknologi Malaysia, 2008